A study on mandarin- learning process for Art & Design Students in UiTM, Malaysia / Nur Afiqah Masrigan and Sharin Mokhtar - Masrigan, Nur Afiqah; Mokhtar, Sharin (Universiti Teknologi MARA, 2021)
Faculty of Art & Design students show a lack of interest in theory-based and facts-based studies such as language-related studies or courses. They are more on solving problems by using imagination and practical skills. In meantime, AD students are required to study a foreign language such as Mandarin but some students opine that learning a third language is the least important. Therefore, a study of the mandarin language is conducted to find the problems faced by lecturers and students in higher learning institutions in the teaching and learning process, specifically in the Mandarin language. The aim is to improve the efficiency in the teaching and learning process for Mandarin learning among higher learning institutions students. Next, quantitative and qualitative research methods were conducted among subject lecturers and AD students. As a result, the study found that the main problem faced by the lecture is related to the student environment factor. For example, students have problems with pronunciation in “Shengmu”, memorizing characters, constructing sentences and writing Chinese characters. Besides that, the lecture has a problem in communication with the student. In addition, the duration provided for Mandarin interaction session is inadequate, and the insufficient materials in the textbook syllabus arouse students‟ difficulties to learn the Mandarin language in the classroom.